Phenolic profile of virgin olive oil from advanced breeding selections - El Riachy, M.; Priego-Capote, F.; Rallo, L.; Luque-de Castro, M. D.; León, L. (Spanish Journal of Agricultural Research, 2012)
The evaluation of the phenolic composition in advanced selections in breeding programs constitutes the first approach for selecting genotypes with improved olive oil quality. In this work, the influence of genotype and ripening index on the phenolic profile of olive oils from advanced selections in comparison to their genitors was studied. Fruit samples were collected in genotypes from crosses between ‘Arbequina’ × ‘Picual’, ‘Picual’ × ‘Arbequina’ and ‘Frantoio’ × ‘Picual’ at five dates from 1st October to 26th November 2009. Characterization of the phenolic profile was performed by liquid–liquid extraction with 60:40 (v/v) methanol–water and subsequent chromatographic analysis with absorption and fluorescence detection in a sequential configuration. A dual effect of genotype and fruit ripening on the phenolic profile has been observed with more pronounced genetic influence in both total (34.73% and 20.45%, respectively) and individual phenols (16.99% to 49.25% and 1.58% to 23.77%, respectively). A higher degree of variability between genotypes at early ripening stages was also observed (p<0.05). The obtained results also allow identification of selections with high content of total and individual phenols. These results suggest a strategy based on early harvesting of fruits (at the first three ripening indexes) for better comparison and selection of genotypes in further crosses in olive breeding programs aiming at improving the quality of virgin olive oil.